Comparative analysis of the complete mitochondrial genomes of three rockfishes (Scorpaeniformes, Sebastiscus) and insights into the phylogenetic relationships of Sebastidae. Issue 12 (23rd December 2020) - Jia, Chenghao; Zhang, Xiumei; Xu, Shengyong; Yang, Tianyan; Yanagimoto, Takashi; Gao, Tianxiang
Abstract: Mitochondrial genome is a powerful molecule marker to provide information for phylogenetic relationships and revealing molecular evolution in ichthyological studies. Sebastiscus species, a marine rockfish, are of essential economic value. However, the taxonomic status and phylogenetic relationships of Sebastidae have been controversial so far. Here, the mitochondrial genomes (mitogenomes) of three species, S. tertius, S. albofasciatus, and S. marmoratus, were systemically investigated. The lengths of the mitogenomes' sequences of S. tertius, S. albofasciatus, and S. marmoratus were 16910, 17056, and 17580 bp, respectively. It contained 13 protein-coding genes (PCGs), two ribosomal RNAs (rRNAs), 22 transfer RNA (tRNA) genes, and one identical control region (D-loop) among the three species. The genetic distance and K a / K s ratio analyses indicated 13 PCGs were suffering purifying selection and the selection pressures were different from certain deep-sea fishes, which were most likely due to the difference in their living environment. The phylogenetic tree was constructed by Bayesian Inference (BI) and Maximum Likelihood (ML). Most interestingly, the results indicated that Sebastidae and Scorpaenidae were grouped into a separate branch, so the taxonomic status of Sebastidae should be classified into subfamily Sebastinae. Our results may lead to a taxonomic revision of Scorpaenoidei.